2007
DOI: 10.1111/j.1365-2141.2007.06903.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A response and dependence in children with acquired aplastic anaemia: a multicentre retrospective study with long‐term observation follow‐up

Abstract: discontinuation: 60% compared to 7AE6% in the slow tapering group (P = 0AE001). Cumulative incidence of MDS/AML was 8% at 10 years, with a significant correlation with both G-CSF cumulative dose and second IST. This long-term follow-up of children with AAA shows that IST with a slow CyA tapering course is an effective treatment with a low-relapse rate in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 29 publications
5
79
1
4
Order By: Relevance
“…A recent Italian study of childhood AA showed a 16% cumulative incidence of relapse, which is comparable with that found in our study. 10 Multivariate analysis of the data from this retrospective multicenter study shows that the use of danazol was the most statistically significant risk factor for relapse. From 1992 to 2007, 441 children with newly diagnosed AA were treated with immunosuppressive therapy consisting of antithymocyte globulin and cyclosporine with (the AA-92 study) or without danazol (the AA-97 study).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Italian study of childhood AA showed a 16% cumulative incidence of relapse, which is comparable with that found in our study. 10 Multivariate analysis of the data from this retrospective multicenter study shows that the use of danazol was the most statistically significant risk factor for relapse. From 1992 to 2007, 441 children with newly diagnosed AA were treated with immunosuppressive therapy consisting of antithymocyte globulin and cyclosporine with (the AA-92 study) or without danazol (the AA-97 study).…”
Section: Discussionmentioning
confidence: 99%
“…9 A report from the Italian Association of Pediatric Hematology and Oncology focused mainly on the response to cyclosporine and dependence after immunosuppressive therapy. 10 A single-center retrospective analysis from the National Institutes of Health showed excellent long-term survival with a 33% cumulative incidence of relapse at 10 years in children with severe AA who responded to the standard immunosuppressive therapy; however, a detailed analysis of relapse that included risk factors was not provided. 11 We previously conducted two prospective multicenter studies: the AA-92 and AA-97, which began in November 1992 and October 1997, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] While ATG is administered as an intravenous infusion over 5 days in hospitalized patients, patients receive CSA orally for 6 months or more. There is controversy about the adequate duration of treatment, as differing recommendations are being made 13 based on little knowledge from clinical trials.…”
mentioning
confidence: 99%
“…A recently published paper by the Italian pediatric group came to the conclusion that CSA tapering was best done over many years to decrease relapse risks. 13 Continuing the study might have been worthwhile if only to shed more light on the important question of the impact of early versus late withdrawal of immunosuppressants. This study again confirms that short-term survival is excellent in these patients (>90%), and this includes obviously some of the patients who do not respond and patients who relapse, as well as the option of rescue bone marrow transplantation in patients in whom a donor can be found.…”
mentioning
confidence: 99%